Sosialisasi Pengolahan Tanaman Kopi dan Pendampingan Pembuatan Produk Selai Kopi: Mendorong Hilirisasi Sumber Daya Desa - Auliyaa Larasati, Annisaa’; Melani Hutajulu, Dinar; Candra Kusuma, Kartika; Fadzillia, Luluk (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
The problem that occurs in Bawang Village is that agricultural products sold in their original form get relatively cheap selling prices. Apart from that, the availability of job opportunities for youth in this village is still very limited. For this reason, there is a need for a process of downstreaming natural resources into value-added products. Apart from getting high prices, the potential for employment opportunities is also wider. The high potential of coffee plant resources and human resources in Bawang Village has encouraged the team to carry out community service activities. The aim of the service is to encourage downstream coffee commodities by providing socialization on coffee plant processing and assistance in making coffee jam products to the Bawang Village community. The methods used are socialization and mentoring. The results of the activity showed an increase in participants' knowledge in the process of processing coffee plants into coffee powder, and an increase in participants' creativity and innovation in making coffee jam products. This activity also fosters enthusiasm and motivation to be able to create new products with added value as an effort to increase people's income. Keywords: coffee processing; coffee jam; hilirization coffee plants; desa bawang.